Advances in Extracting Bioactive Compounds from Food and Agricultural Waste and By-Products Using Natural Deep Eutectic Solvents: A Circular Economy Perspective - Petar Ristivojević; Maja Krstić Ristivojević; Dalibor Stanković; Ilija Cvijetić (Molecules)
Due to the urgent need for a transition to sustainable, zero-waste green technology, the extraction of bioactives from food and agricultural by-products and waste has garnered increasing interest. Traditional extraction techniques often involve using organic solvents, which are associated with environmental and health risks. Natural deep eutectic solvents (NADESs) have emerged as a promising green alternative, offering advantages such as low toxicity, biodegradability, and the ability to dissolve a wide range of biomolecules. This review provides a comprehensive overview of recent trends in the application of NADESs for extracting bioactive compounds from sustainable sources. The review explains the composition and principles of preparation and highlights various applications of NADESs in extracting different classes of bioactive compounds, emphasizing their potential to revolutionize extraction processes. By summarizing the latest advancements and trends, this review aims to support research and industrial applications of NADESs, promoting more sustainable and efficient extraction methods in the food and agricultural sectors.